Session Topic: Lessons of the Penn Central Debacle: Discussion - Bernstein, Peter L. (Journal of Finance, 1971)
Peter L. Bernstein, Session Topic: Lessons of the Penn Central Debacle: Discussion, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 357-358